A Simple Approach to the Fabrication of Graphene-Carbon Nanotube Hybrid Films on Copper Substrate by Chemical Vapor Deposition. Issue 5 (May 2015) - Van Chuc, Nguyen; Thanh, Cao Thi; Van Tu, Nguyen; Phuong, Vuong T.Q.; Thang, Pham Viet; Thanh Tam, Ngo Thi
Abstract : In this study, graphene-carbon nanotube (CNT) hybrid films were directly synthesized on polycrystalline copper (Cu) substrates by thermal chemical vapor deposition (CVD) method. Graphene films were synthesized on Cu substrate at 1000 °C in mixture of gases: argon (Ar), hydrogen (H2 ), and methane (CH4 ). Then, carbon nanotubes (CNTs) were grown uniformly on the surface of graphene/Cu films at 750 °C in mixture of Ar, H2, and acetylene (C2 H2 ) gases. Ferric salt FeCl3 solution deposited onto the surface of graphene/Cu substrate by spin coating method was used as precursor for the growth of the CNTs. The density and quality of the CNTs on the surface of graphene/Cu films can be controlled by varying the concentration of FeCl3 salt catalyst.